Sarana Navigasi Kognitif Sebagai Upaya Peningkatan Kemudahan Evakuasi Pada Bangunan Mal/Fasilitas-Umum - Magda Bhinnety Etsem; Bimo Walgito; - Sugiyanto; - Priyosulistyo (Faculty of Psychology, Universitas Gadjah Mada, 2008)
Mall is a kind of very attractive public facilities that resemble product of technology. In addition to the need of high legibility for optimal use, visitor evacuation with relatively shorter reaction time is desired during emergency situation. The present research is conducted to study: (a) spatial cognition performance of human when short reaction time is demanded, and (b) utilization of such performance with You Are Here (YAH) map as cognitive navi¬gation tool for better emergency responds. The research method contains an expe-rimental work conducted at a real new mall building, involving 160 subjects and 18 experimenters. In this experiment, subjects were assigned to do wayfinding tasks, which covers finding way out through emergency stairs and exit. Prior to wayfinding, subjects were asked to look at a YAH map that has been manipulated in terms of the type (North Up Orientation/NUO or inline egodirec¬tion), and its placement rotation (R0, R45, R90, R135, R180, R225, R270, R315). Subjects were assigned to rank degree of clarity of 3 leaflets containing information of emergency responds at public building, to make scats map for assessing their cognitive map representation ability, and to answer questions related to the information covered in the leaflet. The following conclusions could be drawn: (a) there is a difference in wayfinding (finding way out through emergency stairs and exit) reaction time between YAH map that follow NUO and that of inline egodi¬rection; wayfinding reaction time of inline egodirection map is lower than that of NUO map; (b) there is a difference in the number of direction mistake during wayfinding between YAH map that follow NUO and that of inline egodirection; the number of direction mistake of inline egodirection map is lower than that of NUO map; (c) there is a combination of YAH map type and the way it is placed that results in relatively shorter wayfinding reaction time, i.e.: those that affecting mental rotation equal to zero; (d) there is a kind of leaflet that could be correctly perceived within a relatively short time; (e) in general all subject possess high cognitive map representation ability that could be utilized in cognitive navigation during emergency. Keywords: wayfinding, mental rotation, You Are Here map, cognitive navi-gation, emergency